Development of a Long-Term Ascending Urinary Tract Infection Mouse Model for Antibiotic Treatment Studies - Hvidberg, Hanne (American Society for Microbiology, 2000)
A model of ascending unobstructed urinary tract infection (UTI) in mice was developed to study the significance of the antibiotic concentration in urine, serum, and kidney tissue for efficacy of treatment of UTI in general and pyelonephritis in particular. Outbred Ssc-CF1 female mice were used throughout the study, and Escherichia coli was used as the pathogen. The virulence of 11 uropathogenic E. coli isolates and 1 nonpathogenic laboratory E. coli strain was examined. Strain C175-94 achieved the highest counts in the kidneys, and this strain was subsequently used as the infecting organism. The model gave reproducible bladder infections, i.e., bacteria were recovered from 22 of 23 control mice after 3 days, and histological examination of kidney tissue showed that of 14 infected kidneys, 7 (50%) showed major histological changes, whereas 3 of 36 uninfected kidneys showed major histological changes (P = 0.018). Once the model was established, the efficacies of different doses of cefuroxime and gentamicin, corresponding to active concentrations in urine only or in urine, serum, and kidney tissue simultaneously, were examined. All cefuroxime doses resulted in significantly lower counts in urine than control treatments, but the dose which produced concentrations of cefuroxime only in urine and not in serum or kidney tissue had no effect on kidney infection. Even low doses of gentamicin (0.05 mg/mouse) resulted in concentrations in renal tissue for prolonged times due to accumulation. All gentamicin doses had a significant effect (compared to the effect of the control treatment) on bacterial counts in urine and kidneys. The antibiotic effect on bacterial counts in bladders was negligible for unknown reasons. Use of the mouse UTI model is feasible for study of the effect of an antibiotic in the urinary system, although the missing antibacterial effect in the bladder needs further evaluation.